Probing neutrino emission at GeV energies from compact binary mergers with the IceCube Neutrino Observatory - Abbasi, R; Ackermann, M; Adams, J; Sarkar, S (Cornell University, 2021)
The advent of multi-messenger astronomy has allowed for new types of source searches by neutrino detectors. We present the results of the first search for 0.5 - 5 GeV astrophysical neutrinos emitted from all compact binary mergers, i.e., binary black hole, neutron star black, mass gap and binary neutron star mergers, detected by the LIGO and Virgo interferometers during their three first runs of observation. We use an innovative approach that lowers the energy threshold from ~10 GeV to ~0.5 GeV and searches for an excess of GeV-scale events during astrophysical transient events. No significant excess was found from the studied mergers, and there is currently no hint of a population of GeV neutrino emitters found in the IceCube data.